Effects of basement structural and stratigraphic heritages on volcano behaviour and implications for human activities (the IGCP project 455) - TIBALDI, ALESSANDRO; Lagmay, AMF; Ponomareva, VV (Episodes, 2005)
The IGCP project 455 (2001-2005) is intended to contribute to the comprehension of volcano behavior in different geodynamic settings from a poorly known perspective: the reciprocal influence exerted by volcanoes on their substrate and by the basement on the volcanoes. The main task is to assess the role of this influence in determining natural geological hazards such as eruptions, landslides and earthquakes. The geologic-tectonic control of the substrate on the volcanoes has been usually considered questionable or less important than the conditions of the deep magma source, whereas the control of volcanoes on their basement has even received very little attention. This project improves the comprehension of these phenomena by a strong interdisciplinary approach that ties data on the various geological conditions and heritages of the basement with the deformation processes and geological evolution of different volcanic edifices. We compiled stratigraphic, structural, geomorphological, geophysical, geotechnical, petrographic, geochemical and geochronological data. These data have been transferred to the laboratory-working groups, thus providing realistic numerical and physical simulation even of complex geological structures. Here we present a selection of the main results obtained for some of the studied key volcanoes: Alicudi (Italy) located in a low-tectonic rate setting, Stromboli (Italy) in extensional tectonic setting, Reventador (Ecuador) in compressional setting, and the Northern Volcanic Group of Kamchatka (Russia), Galeras (Colombia) and Mayon (Philippines) in a transtensional setting.